Whole genome sequencing and functional features of a novel biosurfactant-producing Bacillus subtilis UMX-103 / Yousri Abdelmutalab Ahmed Abdelhafiz - Yousri Abdelmutalab, Ahmed Abdelhafiz (2017)
The genus Bacillus is a Gram-positive, aerobic, endospore-forming, rod-shaped bacterium commonly found in the environment that have important industrial, medical, agriculture and environmental values. This study characterized a novel biosurfactant producing bacterial strain UMX-103 which was isolated from a hydrocarbon contaminated site in Terengganu, Malaysia. An integration of both genomics and biochemical approaches were conducted to analyse the biosurfactant production by the strain UMX-103. Determination of biosurfactant production by the strain was conducted using five different assays including; Hemolytic assay, Oil spreading test, Drop-collapse assay, Emulsification assay and Surface tension measurements. The surface tension test showed that the strain is able to lower surface tension up to (26.4 ± 0.02 mN/m). UMX-103 also showed positive results in the other assays. Whole Genome Sequence analysis revealed the genetic contents and genes involved in biosurfactant production. The whole genome was assembled using a combination of both de novo and reference-guided assembly methods. The genome size of UMX-103 is 4,234,627 bp with 4399 genes comprising of 4301 protein-coding genes and 98 RNA genes. The mapping results showed 93.44% of genome similarity with B. subtilis strain 168. The functional annotation analysis revealed present of surfactin biosynthetic gene cluster. This gene cluster belongs to the Non-ribosomal Peptide Synthetase (NRPS) family, which is one of the microbial surfactant groups. A total of 25 genes were identified that involved in biosurfactants production. Among these genes, 14 genes were involved in surfactin biosynthesis and while the remaining genes were involved in surfactin regulation. The comparative genomics and Pangenome analysis of UMX-103 with other Bacillus sp. highlighted unique features of this strain, especially relating to the biosurfactant gene cluster.